An unusual case of bilateral pyoderma gangrenosum with Achilles tendon rupture. (10th December 2014) - Fremlin, G.A.; Rawlings, C.; Livingstone, J.A.; Bray, A.P.J.J.
Summary Pyoderma gangrenosum (PG) is a rare, noninfectious, inflammatory disease characterized by neutrophilic infiltration of the dermis and destruction of tissue. PG is a diagnostic challenge, which can lead to late diagnosis, delayed treatment and detrimental surgical interventions. We describe a presentation not previously reported, affecting deep muscle and tendon leading to tendon rupture. Furthermore, we show the multidisciplinary team approach to management of a patient with PG and the reconstructive surgical element. A 31‐year‐old woman presented with a rapid onset painful, tender, left calf and ankle, which was associated with a mild flare of ulcerative colitis. Investigations revealed a white cell count of 26 × 109 cells L−1, a C‐reactive protein count of 226 mg L−1, no deep vein thrombosis on ultrasound, no bone or joint involvement on X‐ray and no organisms on joint aspirate. Debridement was undertaken after the left ankle developed a foul‐smelling discharging wound. Repeat debridement led to worsening of the condition (pathergy). Intraoperative tissue cultures and microscopy showed no evidence of fungi, bacteria or mycobacteria. Histology showed granulation, inflammatory infiltrate, abscess formation and focal necrotizing vasculitis. Dermatology opinion confirmed PG. Awareness of the diagnosis of PG, and early involvement of dermatology, in a rapidly progressing wound is essential to avoid delayed treatment and prevent worsening through pathergy.